Komunikasi Praktisi Ruqiyah Lembaga Rukyah Syar’iyyah Darussalam Cianjur - Anwar, Ikbalul; Rosyidi, Imron (Prophetica : Scientific and Research Journal of Islamic Communication and Broadcasting, 2017)
The results of this study indicate: 1. Verbal communication used by practitioners uses Indonesian and Sundanese or mixed languages, with soft tones or intonations, and also uses the language of the Qur'an. 2. Non-verbal communication used by ruqyah practitioners in their communication behavior is using body movements, facial expressions, and sucking, as well as how to dress. 3. The motive behind the communication behavior of the performer of ruqyah is the urge to heal people with jinn disorders. 4. Persuasive Communication Persuasive communication is a solid communication process, where individuals or groups show messages, intentionally or unintentionally by verbal and nonverbal ways to obtain a special response from individuals or groups. The conclusion of the communication behavior of ruqyah practitioners to patients at the Ruqyah syar'iyyah Darussalam Institute is to use verbal language where in speaking or reading verbally in a mixed language and the Qur'an, non-verbal communication is movement of the whole body or body language, the motive behind it is encouragement. to cure people affected by genital disorders by using alternative medicine methods in Islam, Ruqyah syar'iyyah Darussalam.